Electronic Library Information System (ELIS) / Cheah Sooi Ping - Cheah , Sooi Ping (2001)
Electronic Library Information System (ELIS) is a computer-based (automation) library system for a secondary school. ELIS consists of a number of smaller systems called subsystems. The modules are acquisition, which enable the System Administrator and Librarians to do ordering and receiving operations: cataloging which enable the creation of a bibliographic database; online cataloging (OPAC) which enables information to be retrieved from the database; circulation which manages the borrowing, returning, renewing, reserving, fine for missing of items· bulletin & feedback which enable the patron to input the feedback regarding the service provided by ELIS and to view the most current bulletin and holiday calendar; and edit module which enable the System Administrator to edit the record in the database from the system interface. This system also provides some additional features such as maintenance on user, reporting password changing, fine system and Online Help to guide the user while using EKIS. The graphical user interface (GUI) features incorporated into the system have made it more appealing and user friendly than other text-based library system. The main development tool used for ELIS is PowerBuilder Ver 5.0. This software maintains the user interface, report and database of this program itself. Iterative Development Methodology is used as model as it allow the developer to move between phases easily and modify the application to evolve with the work environment. ESF's Bar Code 3/9 is used to generate bar code for call number of an item. It is a set of True Type fonts and a utility for implementing code of 9 bar codes. It is easy to use, does not require a checksum, and lets the user code numbers, upper case letters, and some punctuation. ELIS sure can achieve its objectives by fulfilled the functional and nor -functional requirements.